Pengembangan Bahan Ajar Cerita Rakyat Daerah “Sosokan Taba” Berbasis Karikatur untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 03 Kepahiang - Lasmini, Levi; Muktadir, Abdul; Parmadi, Bambang (UNIB Press, 2025)
The purpose of this study was to develop, describe the level of feasibility, find out the user's response and find out the effectiveness of the caricature-based local folklore